Fixed Point of Generalized Weak Contraction in b-Metric Spaces - Maryam Iqbal; Afshan Batool; Ozgur Ege; Manuel de la Sen (Journal of Function Spaces)
In this manuscript, a class of generalized ψ,α,β-weak contraction is introduced and some fixed point theorems in the framework of b-metric space are proved. The result presented in this paper generalizes some of the earlier results in the existing literature. Further, some examples and an application are provided to illustrate our main result.